A variable-temperature X-ray diffraction and theoretical study of conformational polymorphism in a complex organic molecule (DTC). Issue 67 (14th November 2018) - Gionda, Andrea; Macetti, Giovanni; Loconte, Laura; Rizzato, Silvia; Orlando, Ahmed M.; Gatti, Carlo; Lo Presti, Leonardo
Abstract : A small conformational change in the asymmetric unit has a significant effect on how non-covalent interactions determine (i) the crystal packing and (ii) the effect of T on the relative balance of electrostatics and dispersion–repulsions. Abstract : Two conformational crystal polymorphs of 3-diethylamino-4-(4-methoxyphenyl)-1, 1-dioxo-4 H -1λ 6, 2-thiazete-4-carbonitrile (DTC) have been analyzed in the 100 K-room temperature range by single crystal X-ray diffraction and high quality DFT calculations. DTC has strongly polar as well as aliphatic substituents but no hydrogen bonding groups, and thus qualifies as a test molecule for the relative importance of electrostatic vs. dispersion–repulsion terms. The two polymorphs have the same P 21 / n space group and differ by a flipping of the –OCH3 group, the two conformations being almost equi-energetic and separated by a low barrier. The system is monotropic in the observed temperature range with nearly identical thermal expansion coefficients and energy–temperature slopes, one phase consistently predicted to be more stable in agreement with the relative ease of appearance. Energy decompositions show that the electrostatic term is dominant and stabilizes with decreasing temperature. Dispersion and repulsion show the expected behavior, the former becoming more stabilizing at lower temperature in contrast with increasing repulsion at higher density. Absolute values and trends are very similar in the two phases, explaining the small total energy difference. Geometrical analyses of intermolecular contacts using fingerprint plots, as well as the study of molecular dipole moments as a function of T in the framework of the Quantum Theory of Atoms in Molecules, reveal more details of phase stability.